Implementasi Manajemen Syariah Di Dalam Penguatan Manajemen Syariah - Nur Fadilah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Islam as a perfect life system certainly has thoughts about the concept of management. Once the importance of the field of management in terms of economic life, Islam has determined how the actual management process of management. One problem that arises in the management of Islamic management is that the governance mode (management) that is used is the same as conventional institutional management in general, therefore we need innovation in management. The implementation of Syahria management is expected to be able to improve the performance and quality of institutional reviews. Viewed from the perspective of competitors, the Islamic management industry does not consider competitors, who should be defeated or even played. But the concept is every company is able to spur it to be better without having to reduce its competitors. Competitors are partners who succeed in the activities that will be implemented in the field, and not as opponents who are turned off. Implementation of management functions based on Islamic Syahria values.